Spatial distribution of Dechlorane Plus and dechlorane related compounds in European background air - Skogeng, Lovise P.; Lunder Halvorsen, Helene; Breivik, Knut; Eckhardt, Sabine; Herzke, Dorte; Moeckel, Claudia; Krogseth, Ingjerd S. (Frontiers in Environmental Science, 2023)
The highly chlorinated chemical Dechlorane Plus (DP) was introduced as a replacement flame retardant for Mirex, which is banned through the Stockholm Convention (SC) for its toxicity (T), environmental persistence (P), potential for bioaccumulation (B) and long-range environmental transport potential (LRETP). Currently, Dechlorane Plus is under consideration for listing under the Stockholm Convention and by the European Chemical Agency as it is suspected to also have potential for P, B, T and LRET. Knowledge of atmospheric concentrations of chemicals in background regions is vital to understand their persistence and long-range atmospheric transport but such knowledge is still limited for Dechlorane Plus. Also, knowledge on environmental occurrence of the less described Dechlorane Related Compounds (DRCs), with similar properties and uses as Dechlorane Plus, is limited. Hence, the main objective of this study was to carry out a spatial mapping of atmospheric concentrations of Dechlorane Plus and Dechlorane Related Compounds at background sites in Europe. Polyurethane foam passive air samplers were deployed at 99 sites across 33 European countries for 3 months in summer 2016 and analyzed for dechloranes. The study showed that syn- and anti-DP are present across the European continent (<MDL-2.6 pg/m3 and <MDL-12.3 pg/m3, respectively), including parts of the Arctic. This supports that these compounds have potential for long-range atmospheric transport to remote regions. The highest concentrations of Dechlorane Plus were observed in central continental Europe, with anti-DP fractions close to the commercial mixture of Dechlorane Plus. The only detected Dechlorane Related Compounds was Dechlorane-602, which was found in 27% of the samples (<MDL-0.33 pg/m3). The measured concentrations and spatial patterns of Dechlorane Plus and Dechlorane-602 in air across Europe indicate the influence of primary sources of these compounds on background concentrations in European air. Future air monitoring efforts targeting dechloranes is needed in both background and source areas, including consistent temporal trends.